Arabic Language Learning Methods for Early Childhood at RA Nur-Hajijah - Sitorus, Mayang Sari; Srg , Khalida Ziah Sukmana; Tarigan, Salsah Nabilah; Lubis, Hilda zahra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Learning Arabic at an early age plays a significant role in the cognitive, social, and emotional development of children. Beyond being the language used in religious worship by Muslims, Arabic offers numerous advantages in enriching children’s language skills and intellectual abilities. Early exposure to Arabic not only aids in enhancing linguistic abilities but also contributes to the child’s broader understanding of culture and religion. This research aims to investigate the implementation of effective methods for teaching Arabic to young children. The study employs a qualitative approach, using interview guides and observation as primary data collection methods. The findings indicate that the application of engaging methods such as singing, memorization, play, and writing makes the learning process more enjoyable, while also boosting children's enthusiasm and motivation to learn Arabic. These methods help create a more interactive and dynamic learning environment, which fosters a positive attitude towards the language. Ultimately, the research highlights the importance of adopting age-appropriate, enjoyable, and innovative teaching strategies to facilitate early language learning.